Pengelolaan Objek Wisata Tirta Empul oleh Desa Adat Manukaya Let Tampaksiring - Ni Putu Dewi Julianti; I Ketut Sukadana; I Putu Gede Seputra (Jurnal Interpretasi Hukum, 2020)
Indonesia is a country that is well known for the charm of its tourist attractions. The area in Indonesia having the most striking tourist objects is Bali. Bali has been an area known as the island of a thousand temples; the thickness of traditional culture combined with modern culture is its main attraction. One of the tourist objects offering aesthetic value in Bali is Tirta Empul, a place that is believed to be a place for bathing (melukad) with several springs that can make a person’s condition better than earlier. The purpose of this research is two-fold: to examine the management of the Tirta Empul tourist attraction in the Manukaya Let Tampaksiring Customary Village and to reveal the obstacles experienced by the customary villages in maintaining and managing these tourist objects. This study uses a normative legal research design. The results show that the village government made an agreement with the Tourism Office with the aim of developing Tirta Empul tourism attraction and preserving local culture. Some problems or deficiencies in smoothing the goal of cooperation include the lack of intention of the village community in managing the Tirta Empul tourist attraction, equipment and facilities that support cleaning of their respective tourist attractions and the number of tourists who do not pay attention to cleanliness by littering carelessly despite the many trash cans provided, thus creating heas.